Rent movie vocal selections - Larson, Jonathan 1960-1996 (Hal Leonard Corp., 2005)
Sweeping all major theater awards, including the 1996 Pulitzer Prize for drama and four 1996 Tony Awards, "Rent" captures the heart and spirit of a generation, reflecting it onstage through the emotion of its stirring lyrics and the energy of its young cast. Here, in vivid color photos, the complete libretto, original artwork, show artifacts, and oral history, "Rent" comes to life with the behind-the-scenes story of the show's creation
For voice and piano; with chord symbols and guitar chord diagrams
Keywords: Musicals / Excerpts / Vocal scores with piano; Motion picture music / Excerpts / Vocal scores with piano